Determining the prognostic factors of lung cancer data using multiple linear regression analysis / Siti Afiqah Muhamad Jamil and Nurain Ibrahim - Muhamad Jamil, Siti Afiqah; Ibrahim, Nurain Ibrahim (Universiti Teknologi MARA, Kelantan, 2023)
Due to the discovery of numerous cancer types, the risk of mortality among people has significantly increased. In Malaysia, lung cancer is one of the top five cancers that affect both men and women. The purpose of this study is to examine the association between the type of lung cancer and treatment of lung cancer and its associated factors that influence the duration of survival among lung cancer patients. A retrospective cohort study was carried out among lung cancer patients from one of the general hospitals in Johor. The lung cancer data will apply the Chi-Square Test for Independent and Multiple Linear Regression analysis. Several assumptions of model diagnostic prior to data analysis also have been conducted. The results indicated that type and treatment of lung cancer significantly associated towards the duration of survival. Based on descriptive statistics, there is high frequency on male compared to female, Chinese compared to other races, Adenocarcinoma type of Non-Small Cell Lung Cancer (NSCLC) and Chemoradiotherapy (CCRT) compared to other treatments. In short, based on the analysis, it was found that gender and treatment significantly affecting the duration of su1vival of lung cancer patients. Therefore, this will provide insights into which factors are most strongly associated with the prognosis besides, helps in prioritize and rank the importance of different factors.